2011
DOI: 10.4028/www.scientific.net/amm.66-68.146
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Corrosion Behavior of Directionally Solidified FeCoNiCrCu High Entropy Alloy

Abstract: The microstructures of FeCoNiCrCu high entropy alloy were investigated under directional solidification. The results showed that only diffraction peak corresponding to a FCC crystal structure was observed in the directionally solidified FeCoNiCrCu alloy. With increasing solidification rate, the interface morphology would grows in planar, cellular and dendrite. Comparing the potentiodynamic polarization of as-cast and directionally solidified FeCoNiCrCu high entropy alloy in a 3.5%NaCl solution, it is clearly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…The SFE of Cu along the {111} plane is 39 mJ/m 2 , in good agreement with the value reported in literature (41 mJ/m 2 , [26]). Now we start to investigate the SFE of HEA FeCoNiCrCu, which is believed to be FCC phase at room temperature [27,28]. It has 5 types of atoms and the numbers of each type were set as 38, 39, 38, 38, and 39 for Fe, Co, Ni, Cr, Cu, in turn.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…The SFE of Cu along the {111} plane is 39 mJ/m 2 , in good agreement with the value reported in literature (41 mJ/m 2 , [26]). Now we start to investigate the SFE of HEA FeCoNiCrCu, which is believed to be FCC phase at room temperature [27,28]. It has 5 types of atoms and the numbers of each type were set as 38, 39, 38, 38, and 39 for Fe, Co, Ni, Cr, Cu, in turn.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…Additionally, the authors concluded that Mo additions decreased the corrosion resistance of the alloys in a 1 M NaOH solution [24]. Cui et al [25] also confirmed that because they were easily being passivated, the directionally solidified FeCoNiCrCu HEAs were more corrosion-resistant than the as-cast FeCoNiCrCu HEAs in a 3.5 at. % NaCl solution.…”
Section: Introductionmentioning
confidence: 93%
“…% [1][2][3][4]. Many researchers have contributed their efforts to understanding the fabrication, composition, microstructure, and properties of more than 400 HEAs to date [5][6][7][8][9][10][11][12], where the CoCrFeNi system HEAs have been heavily researched, and many studies in the literature have focused on improving the corrosion resistance of CoCrFeNi system HEAs through the addition of other alloy elements, such as Al, Mn, Mo, Cu, and Ti [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Kao et al [14] investigated the electrochemical passive properties of AlxCoCrFeNi alloys by potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), and weight loss tests, indicating that a higher amount of Al in AlxCoCrFeNi alloys was harmful to the corrosion resistance in a 0. solution, and the pitting potentials of Al0.5CrFe1.5MnNi0.5 HEAs were significantly lower than those of Al-free CrFe1.5MnNi0.5 HEAs in a 1 M NaCl solution [15].…”
Section: Introductionmentioning
confidence: 99%
“…YMK yapının oluşumu ikili bileşenlerin YMK yapıda kristalleşmesi durumunda kolaylaşmaktadır. Örneğin AlCoCrFeNi alaşımı A2+B2 yapısı gösterirken Al yerine alaşımda Cu bulunduğunda YMK yapı oluşmaktadır [43,44]. Bu alaşımda CoNi, CoFe, CuNi, CuCo ve FeNi ikililerinin hepsi YMK yapıdadır ve böylece YMK fazı kararlı hale getirir.…”
Section: Yüksek Entropili Alaşımlarda Katı Eriyiklerunclassified